Socialization of Legal Aid for Underprivileged Communities and Legal Awareness Among Youth in Lanto Village, Batupoaro District, Baubau City - Al Hiday Nur; Hasirudin Hasri; Hayun; Wa Ode Novita Ayu Muthmainna (Jurnal Pengabdian Masyarakat Bestari, 2023)
Legal aid institutions were born to help people who are economically and socially disadvantaged, and whose legal knowledge is minimal. Apart from that, the desire to realize the supremacy of law for all citizens, its existence is also very important in society considering the principle of equality before the law. In this community service, we will discuss the Socialization of Free Legal Aid for the Poor as an effort to maximize the free legal aid program for the poor to fulfill access to justice for the less fortunate. The method used in this activity is a directed discussion with the target community. This discussion is attended by all interested elements. Based on the results of the counseling, it was found that there was an increase in knowledge, understanding and ability of the community in Lanto Village, Batu Poaro District regarding free legal aid procedures for the poor.